An Emerging Model for a Farmer Information and Advisory Service for Russia - I. M. Mikhailenko (Journal of Applied Communications, 2002)
The breakup of the Soviet Union in 1991 resulted in the collapse of the centralized “command and control” agricultural information system that told farmers what to plant, when to plant it, and where to deliver the harvest. During the 1990s, a new “Farmer Information and Advisory Service” was launched as part of World Bank and other donor projects. This resulted in the creation of a number of different regional services, some connected with universities, some with agricultural administrations, and some with training institutes. These really constitute “fragments” created to suit regional needs rather than potential models for a future national agricultural communication and extension system. However, important lessons have been learned from these experiments. Using experiences from other countries and Russia’s recent experiences, a model for a new agricultural communication and extension system is proposed that would fit Russia’s unique agricultural structure and extensive geography.